Computational approaches for drug repurposing in oncology: untapped opportunity for high value innovation - Dalwadi, Shraddha M.; Hunt, Andrew; Bonnen, Mark D.; Ghebre, Yohannes T. (Frontiers in Oncology, 2023)
Historically, the effort by academia and industry to develop new chemical entities into lifesaving drugs has limited success in meeting the demands of today's healthcare. Repurposing drugs that are originally approved by the United States Food and Drug Administration or by regulatory authorities around the globe is an attractive strategy to rapidly develop much-needed therapeutics for oncologic indications that extend from treating cancer to managing treatment-related complications. This review discusses computational approaches to harness existing drugs for new therapeutic use in oncology.